PARTISIPASI MASYARAKAT MUSLIM DALAM PENDIDIKAN SEBAGAI IMPLEMENTASI HIFDZ AL-‘AQL DAN ICESCR - Madaniy, A Malik (Sunan Kalijaga State Islamic University & The Asia Foundation, 2016)
This paper asserts that education is an important instrument in life. Specifically, this article describes the rationale for Muslim’s obligation to participate actively in education, and the roles they play in the implementation of a quality education. All will be assessed from the perspective of Islamic teachings, particularly the Qur’an and Hadith. In addition, to strengthen and complement this paper, the perspective of the International Covenant on Economic, Social and Cultural Rights (ICESCR), which confirms that the Islamic community is a unified living entity when it comes to fulfilling education (kiyan hayy wahid). Therefore, the cooperation of various parties in the administration of education in accordance with the principles of maqasid shariah and the ICESCR is part of the Qur’anic command to do good deeds and piety (ta’awun ‘ala al-birr wa at -taqwa). Cooperation should embodied in an effort to develop a culture of reading and writing, preparing facilities and infrastructure, to increase educational human resources and create an environment conducive to education. Contribution of the Muslim community in educational issues should be the expectation of all parties.